2015
DOI: 10.1021/acs.jpcc.5b08730
|View full text |Cite
|
Sign up to set email alerts
|

Water Transport in MgSO4·7H2O During Dehydration in View of Thermal Storage

Abstract: The water phases in a MgSO4·7H2O crystal during heating were studied with the help of NMR. The thermogravimetric analysis (TGA) data showed that the heating rate has a strong effect on the dehydration process. NMR experiments showed that pore water, i.e., an aqueous solution of MgSO4, was produced during dehydration. Additional NMR measurements indicate a water diffusion coefficient of this pore water that is 10 times lower than that of bulk water. We showed on the basis of a model that pore water is produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 32 publications
2
55
1
Order By: Relevance
“…The hydrolysis 48 In the lack of experimental study for the diffusion of H 2 O through MgCl 2 hydrates, we compared with the H 2 O diffusivity through other TCM epsomite (MgSO 4 Á7H 2 O). 49 Zhang et al 49 has reported the same order of magnitude for the diffusivity of H 2 O in the center of the MgSO 4 .7H 2 O. Donkers et al 50 has measured the DC of water in epsomite using NMR. They reported the DC in range of 10 À10 to 10 À9 m 2 s À1 in the temperature range of 293 to 413 K. In the light of their experimental and simulation results of water diffusion in other heat storage material (MgSO 4 Á7H 2 O), we can conclude that the present ReaxFF-MD simulations could mimic the water transport in MgCl 2 hydrates.…”
Section: Reaxff-md Simulations Of Mgcl 2 Hydratesmentioning
confidence: 88%
See 2 more Smart Citations
“…The hydrolysis 48 In the lack of experimental study for the diffusion of H 2 O through MgCl 2 hydrates, we compared with the H 2 O diffusivity through other TCM epsomite (MgSO 4 Á7H 2 O). 49 Zhang et al 49 has reported the same order of magnitude for the diffusivity of H 2 O in the center of the MgSO 4 .7H 2 O. Donkers et al 50 has measured the DC of water in epsomite using NMR. They reported the DC in range of 10 À10 to 10 À9 m 2 s À1 in the temperature range of 293 to 413 K. In the light of their experimental and simulation results of water diffusion in other heat storage material (MgSO 4 Á7H 2 O), we can conclude that the present ReaxFF-MD simulations could mimic the water transport in MgCl 2 hydrates.…”
Section: Reaxff-md Simulations Of Mgcl 2 Hydratesmentioning
confidence: 88%
“…The activation energy and preexponential factor for H 2 O diffusion in MgCl 2 ÁH 2 O is higher than MgCl 2 Á2H 2 O, thus the net effect of the temperature on DC of H 2 O through MgCl 2 ÁH 2 O is similar to MgCl 2 Á2H 2 O. We have fitted the data on water-transport through the epsomite in the temperature range of 293 to 413 K. 50 The DC follows the Arrhenius equation. The activation energy and pre-exponential factor are 5.7 Â 10 À4 m 2 s À1 and 42.6 kcal mol À1 .…”
Section: Reaxff-md Simulations Of Mgcl 2 Hydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Donkers has studied the water transport on 1-2 mm crystal of heptahydrate of magnesium sulfate by NRM analysis in dynamic condition under dry N 2 atmosphere [22]. This analysis allows to show that liquid water is formed in the pore of crystal during dehydration at 48 °C due to local increase of the water vapor pressure.…”
Section: Mgso 4 (S) + 7h 2 O (G) ↔ Mgso 4 • 7h 2 O (S)mentioning
confidence: 99%
“…However, not every salt shows better thermochemical heat storage properties. Several literatures have been reported for contemplated the demand of TCMs on the basis of high dehydration/hydration enthalpy, easily achievable reaction temperature (<150°C), material cyclability, toxicity and cost 26 . Previous studies reported that MgSO 4 7H 2 O has the potentially to store space heat energy for long term.…”
Section: Introductionmentioning
confidence: 99%